Methods to Increase the Protective Effectiveness of Add-on Armour made of Perforated Ultra-High-Strength Nanobainitic Steel Plates - Bogdan GARBARZ; Jarosław MARCISZ; Wojciech BURIAN; Aleksander KOWALSKI; Jacek BOROWSKI; Szymon SZKUDELSKI; Marek WALICKI; Kamil ZAJĄC (Problemy Mechatroniki)
The mechanical properties of industrially produced perforated steel plates are obtained by hardening and low-temperature tempering to produce a martensitic microstructure. Another morphological type of steel microstructure that allows for ultra-high strength and, at the same time, a level of ductility that qualifies it for use in armour is nanobainite. Research into nanobainitic steels has led to the development of plates manufacturing technology at a level that can be implemented in industrial production, and has confirmed the high potential of this material for use as additional armour in the form of perforated plates. This paper reports the results of research aimed at developing a technology for the production of perforated armour plates made of nanobainitic steel, with properties competitive with currently available perforated steel plates on the world market with the highest protective effectiveness under conditions of multi-hit firing tests with small and medium calibre ammunition. The tests were performed on 300 260 mm plates, with the nominal thicknesses of 8 mm, 6 mm and 4 mm, produced from industrially melted nanobainitic steel NANOS-BA. The protective effectiveness of nanobainitic perforated plates in a system with a solid armour steel backing plate of 500 HBW hardness was tested by multi-hit firing, according to the procedures set out in the STANAG 4569 and AEP-55 vol. 1 specifications (adapted to the format of tested plates), against selected projectile types assigned to protection levels 2 and 3. Based on the analysis of the results of the firing tests and the macroscopic and microscopic examinations of the perforated plates before and after firing, the optimum perforation method was selected and the most favourable geometrical and dimensional arrangements of the perforations were determined for different plate thicknesses.